Fast-forwarding evolution—Accelerated adaptation in a proofreading-deficient hypermutator herpesvirus. Issue 2 (14th October 2022) - Xing, Na; Höfler, Thomas; Hearn, Cari J; Nascimento, Mariana; Camps Paradell, Georgina; McMahon, Dino P; Kunec, Dusan; Osterrieder, Nikolaus; Cheng, Hans H; Trimpert, Jakob
Abstract: Evolution relies on the availability of genetic diversity for fitness-based selection. However, most deoxyribonucleic acid (DNA) viruses employ DNA polymerases (Pol) capable of exonucleolytic proofreading to limit mutation rates during DNA replication. The relative genetic stability produced by high-fidelity genome replication can make studying DNA virus adaptation and evolution an intensive endeavor, especially in slowly replicating viruses. Here, we present a proofreading-impaired Pol mutant (Y547S) of Marek's disease virus that exhibits a hypermutator phenotype while maintaining unimpaired growth in vitro and wild-type (WT)-like pathogenicity in vivo . At the same time, mutation frequencies observed in Y547S virus populations are 2–5-fold higher compared to the parental WT virus. We find that Y547S adapts faster to growth in originally non-permissive cells, evades pressure conferred by antiviral inhibitors more efficiently, and is more easily attenuated by serial passage in cultured cells compared to WT. Our results suggest that hypermutator viruses can serve as a tool to accelerate evolutionary processes and help identify key genetic changes required for adaptation to novel host cells and resistance to antiviral therapy. Similarly, the rapid attenuation achieved through adaptation of hypermutators to growth in cell culture enables identification of genetic changes underlying attenuation and virulence, knowledge that could practically exploited, e.g. in the rational design of vaccines.